Evidence-based practice in local public health service in Ghana. Issue 1 (1st January 2017) - Owusu-Addo, E.; Cross, R.; Sarfo-Mensah, P.
Abstract: While the role of evidence-based public health in improving health outcomes is frequently touted, there remains a dearth of research examining the use of evidence in public health service particularly in low- and middle-income countries. Therefore, the aim of this research was to examine the use of evidence in local public health service in Ghana, a lower middle-income country. Semi-structured in-depth interviews were conducted with local health managers from 11 District Directorates of Health in Ashanti Region. Three organising themes emerged from the interview transcripts: understanding of evidence-based public health; the process of using evidence; and the value of evidence in public health practice. The study suggests that though evidence-based practice was not new to the local health managers, its application was very low. The process of using evidence commenced with making a decision about the direction of a programme which had been already prioritised and planned by other high-level actors and then various sources of information, including available research evidence, were used to justify the decision. The study has revealed that there is an urgent need for pre-service and in-service training programmes that build and maintain common skill sets and language among local public health practitioners in Ghana to accomplish evidence-based public health goals. Similarly, giving local health managers flexibility to prioritise and make decisions would result in increased uptake of evidence in local public health service.